A Critique and Analysis of Jurisprudential References to Verses 3 and 129 of Surah An-Nisa As to Justice Among Spouses - Mohadese Moghimy Nejad Davarani (فقه و حقوق خانواده)
Although the principle of justice among spouses is a mandatory obligation in the Islamic religion, its specific boundaries are subject to debate. Verses 3 and 129 of Surah An-Nisa, which address the issue of polygyny and justice among women, constitute a part of the Shia jurists' evidence on this matter. Given the fundamental role of the Quran as a source of Islamic law and the inadequacies of some jurists' arguments based on these verses, the present study employs a descriptive-analytical method to critique and analyze these references. The findings indicate that verse 3 emphasizes the necessity of providing mandatory alimony for all wives, while verse 129 prohibits disregarding women's emotional and sexual needs. Some jurists' arguments that verse 3 supports the desirability of equal distribution of alimony among wives or linking this verse to the obligation of equal division of nights are subject to criticism. Furthermore, the argument of some jurists that verse 129 does not necessitate equality in alimony or the right of nights, or even in heartfelt affection, is not acceptable.